Tourist experience at port and town: assessing cruiser satisfaction during self-organized onshore excursions at Lautoka Port, Fiji, in 2018–2019. Issue 5 (May 2022) - Kundra, Sakul; Kushwah, Shailendra Singh; Kundra, Nakul; Nabobo-Baba, Unaisi; Alam, Mumtaz; Alam, Mohammad Afsar
Abstract: Fiji is regarded as a South Pacific paradise; it attracts many tourists and cruisers desirous of a one-of-a-kind, memorable and long-lasting experience. The archipelago has witnessed an unprecedented rate of development in the cruise industry in the last decade, with an increase in the number of cruise liners as well as cruisers, especially those who take a halt for less than a half-day at a port and thus gain experience as tourists in Fiji. Cruisers opt for either pre-booked tours (booking made before disembarking) or self-organized excursions. Their experience during self-organized excursions at Fiji ports has not been studied so far. This study attempts to fill in this research gap. The study carries out a statistical analysis of the empirical data on cruisers' feedback on onshore experiences. This data was collected through a questionnaire survey of 369 cruisers who enjoyed self-organized excursions at Lautoka port anytime between December 2018 and April 2019. The study uses a Likert-type scale to measure cruiser's satisfaction; it carries out principal component analysis with Varimax Kaiser normalization and SPSS (demo); it further uses a factor analysis model to make observations. The results of this study indicate that cruiser satisfaction and behaviour are positively or adversely affected by many socio-cultural and economic factors. The study puts forward some constructive suggestions to achieve high satisfaction among cruisers. Abstract : Cruise liners; Cruiser onshore experience; Cruiser satisfaction; Cruise vacation; Self-organized excursions; Lautoka wharf.